The Chylomicron: Relationship to Atherosclerosis - Gerald H. Tomkin; Daphne Owens (International Journal of Vascular Medicine)
The B-containing lipoproteins are the transporters of cholesterol, and the evidence suggests that the apo B48-containing postprandial chylomicron particles and the triglyceride-rich very low density lipoprotein (VLDL) particles play an important part in the development of the plaque both directly and indirectly by their impact on LDL composition. The ratio of dietary to synthesised cholesterol is variable but tightly regulated: hence intervention with diet at best reduces serum cholesterol by <20% andusually <10%. Statins are the mainstay of cholesterol reduction therapy, but they increase cholesterol absorption, an example of the relationship between synthesis and absorption. Inhibition of cholesterol absorption with Ezetimibe, an inhibitor of Niemann Pick C1-like 1 (NPC1-L1), the major regulator of cholesterol absorption, increases cholesterol synthesis and hence the value of adding an inhibitor of cholesterol absorption to an inhibitor of cholesterol synthesis. Apo B48, the structural protein of the chylomicron particle, is synthesised in abundance so that the release of these particles is dependent on the amount of cholesterol and triglyceride available in the intestine. This paper will discuss cholesterol absorption and synthesis, chylomicron formation, and the effect of postprandial lipoproteins on factors involved in atherosclerosis.